Rare bird documentation form for Peregrine Falcon at Sand Point at Coralville Reservoir, 1976 - Newlon, Michael C.et al (1976)
Rare bird documentation form for a Peregrine Falcon at Sand Point at Coralville Reservoir in Johnson County, IA on September 26, 1976. Epson - sheet feed/flatbed